2022
DOI: 10.3390/pharmaceutics14020352
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab Decorated Nanoparticles Enhance Antibody Stability and Therapeutic Outcome in Epithelial Colitis Targeting

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory disease of the gastrointestinal tract with increasing incidence worldwide. Although a deeper understanding of the underlying mechanisms of IBD has led to new therapeutic approaches, treatment options are still limited. Severe adverse events in conventional drug therapy and poor drug targeting are the main cause of early therapy failure. Nanoparticle-based targeting approaches can selectively deliver drugs to the site of inflammation and reduce the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In the inflammation state, the activity of proteases is strongly upregulated contributing to the pathogenesis of colitis, 48 which can lead to an inactivation of the antibody. However, Ries et al 49 showed that covalent immobilization of antibodies on NPs strongly enhanced their stability against proteolytic degradation. This is also in line with the results of this study, sufficiently high binding ability of anti-MUC5 was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…In the inflammation state, the activity of proteases is strongly upregulated contributing to the pathogenesis of colitis, 48 which can lead to an inactivation of the antibody. However, Ries et al 49 showed that covalent immobilization of antibodies on NPs strongly enhanced their stability against proteolytic degradation. This is also in line with the results of this study, sufficiently high binding ability of anti-MUC5 was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…To construct LFA‐1 modified SPIO nanoparticles, first, oleic acid capped SPIO nanocrystals were encapsulated with a layer of phospholipid consisting of 80% n‐poly(ethylene glycol) phosphatidylethanolamine (DPPE‐PEG) and 20% dioleoyl‐glycero‐succinyl‐nitrilotriacetic acid (DOGS‐NTA). Then, the LFA‐1 I domain with His tag was conjugated with nickel ions robustly chelated by amide bonds via high affinity to attain the targeted SPIO nanoparticles 69,107–110 …”
Section: Methods To Combine Targeting Moiety With Core Nanoparticlesmentioning
confidence: 99%
“…Then, the LFA-1 I domain with His tag was conjugated with nickel ions robustly chelated by amide bonds via high affinity to attain the targeted SPIO nanoparticles. 69,[107][108][109][110]…”
Section: Covalent Coupling Of Ligands To Drug Loaded Nanoparticlesmentioning
confidence: 99%